‘When I look at this van, it’s not only a van’: symbolic objects in the policing of migration - Lowndes, Vivien; Madziva, Roda (Sage, 2016)
The ‘Go Home Van’ was the centrepiece of the UK government’s 2013 immigration enforcement campaign. Vehicles were driven around ethnically diverse London neighbourhoods clad with giant posters offering irregular migrants a choice between ‘voluntary departure’ and criminal arrest. Abandoned shortly afterwards in response to complaints, the GHV nonetheless had a significant impact on migrants. Through interviews and focus groups, this article investigates what was conveyed by the van, and the means by which it achieved these effects. We find that the GHV communicated meanings about the illegitimacy and criminality of migrants, with its material characteristics (visibility and mobility) as important as the words and pictures on its surface. Migrants sought to resist the van through hiding, while support organisations rejected dominant meanings and crafted alternatives. The article establishes a research agenda around the wider role of symbolic objects, in the context of the global migration crisis.